Regional Taxes as a Pillar for Increasing PAD: Analysis of Effectiveness, Contribution, and Efficiency in North Maluku Province - Muhammad Khotib; Muhammad Hasnin (Apollo: Journal of Tourism and Business, 2026)
This study aims to strengthen fiscal independence by increasing the effectiveness of tax revenue, administrative efficiency, and taxpayer awareness, so that regional taxes truly become a pillar of increasing regional revenue (PPH) in North Maluku. The type of data used is secondary data in the form of reports on the realization of the State Revenue and Expenditure Budget (PPH), specifically data on regional tax revenue, PPH, and tax revenue costs for the 2020–2024 period. Data were obtained from official documents of the Regional Financial Management Agency (BAPENDA) and publications from the Central Statistics Agency (BPS). The data analysis method was carried out in three stages. First, effectiveness analysis, namely by calculating the ratio of regional tax realization to the regional tax target. Second, contribution analysis, namely by calculating the ratio of regional tax realization to total PPH. Third, efficiency analysis, namely by calculating the ratio between revenue costs and regional tax realization. The results of the analysis were then categorized based on the effectiveness, contribution, and efficiency assessment standards commonly used in regional financial research.